Submicron ne atlantic marine aerosol chemical composition and abundance: seasonal trends and air mass categorization ... - Ovadnevaite, Jurgita; Ceburnis, Darius; Leinert, Stephan; Dall'Osto, Manuel; Canagaratna, Manjula; O'Doherty, Simon; Berresheim, Harald; O'Dowd, Colin (Wiley-Blackwell, 2014)
Three years of continuous Aerosol Mass Spectrometry measurements at the Mace Head Global Atmosphere Watch research station revealed seasonal patterns in the chemical composition of submicron NE Atlantic marine aerosol as well as distinct chemical signatures associated with marine air masses of different origin (i.e., polar, Arctic, or tropical). Concentrations of secondary inorganic aerosol species and both primary and secondary organic compounds were closely related to oceanic biological activity and ranged from low median mass concentrations during winter to high median values during summer as follows: 0.025-0.9 mu gm(-3) for nonsea-salt sulfate (nss-sulfate), 0.025-0.4 mu gm(-3) for organic matter, 0-0.09 mu gm(-3) for methanesulfonic acid (MSA). Sea-salt concentrations illustrated an opposite pattern with the highest median value being observed during winter (0.74 mu gm(-3)) and lowest during summer (0.08 mu gm(-3)). Maritime polar air masses typically featured the highest concentrations of sea salt and ...